Agarose cell block technique as a complementary method in the diagnosis of fungal osteomyelitis in a dog - Zanoni, Diogo Souza [UNESP]; Grandi, Fabrizio [UNESP]; Cagnini, Didier Quevedo [UNESP]; Bosco, Sandra de Moraes Gimenes [UNESP]; Rocha, Noeme Sousa [UNESP] (My University, 2012)
A 7-year-old Labrador Retriever female dog presenting left forelimb lameness for one day was admitted to the Veterinary Hospital (UNESP-Botucatu) for clinical evaluation. Several tests, including blood and image analysis, microbiological culture and cytology of lytic areas of affected bone were made in order to establish a diagnosis. Serum biochemical profile revealed increased levels of liver enzymes, plasma globulin, creatine kinase (CK) and calcium. Hemogram revealed anemia and leukocytosis; left humerus image analysis revealed an osteolytic lesion and cytology revealed a suppurative periostitis. Differential diagnosis was a nonspecific infectious inflammatory process or osteosarcoma. Since it was not possible to achieve a definitive diagnosis and there was a highly suspicious for an infectious agent, an agarose cell block of the bone marrow fine-needle aspiration was made. The cytological examination of cell block presented similar findings as described previously. However, additional stains including periodic acid-Schiff (PAS) were positive for fungal hyphae, which rendered a diagnosis of fungal osteomyelitis due to Aspergillus spp. This case report illustrates an uncommon cause of osteomyelitis for breed that was diagnosed by an underused method in veterinary medicine.
Keywords: Aspergillosis; Bone; Cell block; Cytology; Dog